Colistin Resistance in Critically Ill Adults: A Systematic Review of Epidemiological, Clinical, Laboratory, and Molecular Evidence - Eugen Mihail Arnautu; Elena Leocadia Plesea; Ovidiu Mircea Zlatian; Georgiana Cristiana Camen; Radu Razvan Mititelu; Andrei Osman; Maria-Loredana Tieranu; Andreea Loredana Golli; Alice Elena Ghenea (Microorganisms, 2026)
Colistin resistance is an increasing concern in critically ill adults, but reported rates, clinical consequences, laboratory detection, and resistance mechanisms vary widely between studies. This systematic review evaluated epidemiological, clinical, laboratory, and molecular evidence on colistin resistance in adult intensive care populations. MEDLINE/PubMed, the Cochrane Library, Scopus, and Web of Science Core Collection were searched, and the findings were synthesised descriptively because of substantial differences between studies. A total of 120 studies were included. In studies using BMD in broader ICU populations, colistin non-susceptibility ranged from approximately 0.3–57.4% at the isolate level, while patient-level carriage/acquisition estimates ranged from approximately 1.2% to 9.4%. Clinical studies often reported poorer outcomes in patients with colistin-resistant infections. However, the strength and direction of these associations were inconsistent, and most comparative analyses had substantial risk of bias. Laboratory methods influenced resistance detection, while heteroresistance required specific testing approaches. Molecular studies identified several resistance pathways, including mcr genes, mgrB disruption, regulatory alterations, clonal spread, and within-host evolution. Overall, colistin resistance in critical care is highly heterogeneous and should be interpreted according to the clinical, microbiological, and epidemiological context.